PERAN DINAS SOSIAL KOTA SEMARANG DALAM MENINGKATKAN KESEJAHTERAAN DISABILITAS - Cahyani, Meyfita Esti; Sulandari, Susi; Hariani, Dyah (Journal of Public Policy and Management Review, 2021)
People with disabilities who are included in the DTKS (Integrated Data on Social Welfare) of Semarang City in 2020 are 3,243 people while the total number of people with disabilities in Semarang City is 5,800 people. This problem certainly requires the role of the Semarang City Social Service to improve the welfare of the disabled community. The purpose of this study is to describe and analyze the role of the Semarang City Social Service in improving the welfare of people with disabilities and their driving and inhibiting factors. This research method is descriptive qualitative. The data collection techniques of this research are observation, interview, documentation and literature study. Determination of the subject in this study was done by purposive sampling method. The theory used is the role theory according to Jam Ife and Frank Tesoriero covering facilitative, educational, representative and technical roles. The results of the research conducted are that the role of the Semarang City Social Service in improving the welfare of the disabled community is quite good. The role that is not well implemented is the four role indicators, namely the facilitative role. The driving factors for the role of the Semarang City Social Service in improving the welfare of the disabled community consist of competence, socialization and role behavior while the inhibiting factors are role transition and role distance.